2020
DOI: 10.1038/s41467-020-19475-5
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol abolishes vigilance-dependent astroglia network activation in mice by inhibiting norepinephrine release

Abstract: Norepinephrine adjusts sensory processing in cortical networks and gates plasticity enabling adaptive behavior. The actions of norepinephrine are profoundly altered by recreational drugs like ethanol, but the consequences of these changes on distinct targets such as astrocytes, which exhibit norepinephrine-dependent Ca2+ elevations during vigilance, are not well understood. Using in vivo two-photon imaging, we show that locomotion-induced Ca2+ elevations in mouse astroglia are profoundly inhibited by ethanol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(69 citation statements)
references
References 72 publications
(97 reference statements)
3
65
0
1
Order By: Relevance
“…Two recent studies independently generated transgenic mouse lines with LoxP sites flanking Adra1a , allowing conditional deletion of the gene in astrocytes by crossing to appropriate Cre drivers. Both found a loss of calcium transients evoked by enforced locomotion (i.e., a form of startling), or noxious stimuli, in cerebellar ( Ye et al, 2020 ) and spinal cord astrocytes ( Kohro et al, 2020 ), respectively. This is consistent with the transcriptome data from astrocytes isolated from these regions ( Anderson et al, 2016 ; Boisvert et al, 2018 ).…”
Section: Noradrenergic Receptors In the Cnsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two recent studies independently generated transgenic mouse lines with LoxP sites flanking Adra1a , allowing conditional deletion of the gene in astrocytes by crossing to appropriate Cre drivers. Both found a loss of calcium transients evoked by enforced locomotion (i.e., a form of startling), or noxious stimuli, in cerebellar ( Ye et al, 2020 ) and spinal cord astrocytes ( Kohro et al, 2020 ), respectively. This is consistent with the transcriptome data from astrocytes isolated from these regions ( Anderson et al, 2016 ; Boisvert et al, 2018 ).…”
Section: Noradrenergic Receptors In the Cnsmentioning
confidence: 99%
“…It should also be noted that none of the studies performed in mouse visual cortex that we cite unambiguously demonstrate the direct activation of astrocyte α1-NAR to be central to the observed effects. Even if this is the most likely explanation, it remains to be explored in future studies, likely employing the Adra1a -floxed mouse lines that were recently reported ( Kohro et al, 2020 ; Ye et al, 2020 ).…”
Section: α1-nar Triggered Calcium Signaling In Astrocytes: a Switch Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, two-photon calcium imaging is beginning to identify how systemically injected ethanol modulates neuromodulator release and non-neuronal cell types 75 .…”
Section: Discussionmentioning
confidence: 99%